Effect of the age of visual impairment onset on employment outcomes in South Korea: analysis of the national survey on persons with disabilities data - Boyoung Jeon; Heejo Koo; Hye-Jae Lee; Euna Han (BMC, 2022)
Abstract Background Opportunities for paid employment provide meaningful ways for those with disabilities to participate in society and achieve financial independence. Although the onset age of disabilities can alter individuals' attitudes toward accepting their disabilities and their desire for work, the lack of data limits relevant empirical research. The purpose of this study is to examine the effect of the onset age on employment, job security (permanent vs. temporary), and wage level among visually impaired adults in South Korea. Methods We used three years of the National Survey on Persons with Disabilities data, 2011, 2014, and 2017, and included 583 participants in this study. We used a logistic regression model for the employment status and a multinomial logistic regression model for job security. We analyzed log monthly wage by a multivariate linear regression model, which subdivided the age groups, with 20-49 years old denoting prime-aged (n = 245) and 50-64 years old denoting late-middle-aged (n = 338). For each age group, we conducted a sub-analysis by sex. Results For prime-aged adults, the employment probability decreased as the age of visual impartment onset increased, and women in particular experienced a lower employment rate for both permanent and temporary jobs when their disability onset age was above 25. However, among permanent employees, monthly wages were higher if the onset age was 25 + compared to when the onset age was 0-5 years old. In late middle-aged adults, adult onset disabilities were associated with higher odds of employment and higher wages for temporary jobs, implying these individuals worked unskilled or manual jobs. Conclusions In prime-aged adults, higher monthly wages among permanent employees showed that they were more likely to continue their original work, whereas in late-middle-aged adults, adult-onset disabilities were associated with a higher employment rate and higher wages for temporary jobs, suggesting the need for further investigation into job quality. These findings indicate a need for differentiated policy approaches considering the onset age of visual impairment to improve labor market outcomes throughout individuals' lifespans.